Sources of Slavic Pre-Christian Religion / ed. J. A. Alvarez-Pedroza. Leiden; Boston: Brill, 2021. 548 p. ISBN 978-90-04-44061-6 - Vladimir Petrukhin (Славянский мир в третьем тысячелетии, 2022)
The review is dedicated to the fi rst publication of a complete set of sources on the Slavic pre-Christian religion. The form of anthology with parallel texts in the original language and an English translation, chosen by publishers, provides an opportunity for comparative analysis of texts provided with general numbering. Essential for this analysis are the works of the Russian experts in Slavic studies — representatives of semiotic and ethnolinguistic trends of research, publishers of ancient sources on the Slavs’ beliefs.